2021
DOI: 10.3329/jbcps.v39i2.52410
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Unstable Thoracolumbar Fracture Following Long Segment Posterior Fixation

Abstract: Introduction: Fractures of the thoracolumbar region are the most common injuries of the vertebral column and burst fractures are the most frequent. The purpose of this study was to see the radiological and functional outcome after long segment posterior fixation in unstable thoracolumbar spine injury with incomplete neurological deficit. Methods: A total of 146 cases were included in this prospective case series from January 2014 to December 2018 through non randomized purposive sampling. All the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The time interval from injury to surgery time was 5.5 days for one of the studies, 18 and 14-21 days for the other one. 14 It was 2.87±1.97 days in our study and 1 day in a study. 23 Studies have shown better outcomes with less interval from injury to surgery.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…The time interval from injury to surgery time was 5.5 days for one of the studies, 18 and 14-21 days for the other one. 14 It was 2.87±1.97 days in our study and 1 day in a study. 23 Studies have shown better outcomes with less interval from injury to surgery.…”
Section: Discussionsupporting
confidence: 50%
“…The final VAS score in our study was 14.37±12.08 which was similar to the final VAS score of 16.4±8.9 in the study. 14 The VAS score was lower in other studies. 11 , 26 A total of 27 (90%) cases in our study had mild pain and 3 (10%) had moderate pain at the final follow-up.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations